2013
DOI: 10.1118/1.4790564
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a free‐running synchronization artifact correction for MV‐imaging with aSi:H flat panels

Abstract: The presented free-running sync correction method improves SNR of single frames and enables imaging applications, like low-dose rate imaging at increased image frame rates (e.g., to track moving gold fiducials in the lung). Adaptive image guided radiotherapy protocols become even feasible in VMAT plans. Also simultaneous kilovolt and MV imaging applications can benefit from new possibilities of MV scatter removal in x-ray images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Based on the results of static marker detection reported in Table I, it was shown that the detrimental effect of pulsing artifacts on marker detection success was increased in function of frame rates. This confirmed the hypothese from Mooslechner et al 20 that the effect of pulsing artifacts increases for higher frame rates like, 30 Hz on the XRD 1642 AP19. With the availability of high frame rate MV imaging, research on pulsing artifact suppression is gaining importance.…”
Section: Hzsupporting
confidence: 90%
See 4 more Smart Citations
“…Based on the results of static marker detection reported in Table I, it was shown that the detrimental effect of pulsing artifacts on marker detection success was increased in function of frame rates. This confirmed the hypothese from Mooslechner et al 20 that the effect of pulsing artifacts increases for higher frame rates like, 30 Hz on the XRD 1642 AP19. With the availability of high frame rate MV imaging, research on pulsing artifact suppression is gaining importance.…”
Section: Hzsupporting
confidence: 90%
“…With respect to the maximum field size of 15 × 15 cm 2 on the Vero system, a small line artifact was reintroduced during electronic synchronized readout for in-air open beam MV images in function of smaller field sizes. Based on quantitative evaluation using Mooslechner's SNR, 20 the field size dependent line artifact during synchronized readout was considered to be a second order image degradation effect with respect to pulsing artifacts experienced during free running MV imaging. To our knowledge, a line artifact during synchronized readout with START-STOP, that is function of the field size, was not described before in literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations